High-End Scenarios of Sea-Level Rise for Coastal Risk-Averse Stakeholders - Dayan, Hugo; Le Cozannet, Goneri; Speich, Sabrina; Thiéblemont, Rémi (Frontiers in Marine Science, 2021)
Sea-level rise (SLR) will be one of the major climate change-induced risks of the 21st century for coastal areas. The large uncertainties of ice sheet melting processes bring in a range of unlikely - but not impossible - high-end sea-level scenarios (HESs). Here, we provide global to regional HESs exploring the tails of the distribution estimates of the different components of sea level. We base our scenarios on high-end physical-based model projections for glaciers, ocean sterodynamic effects, glacial isostatic adjustment and contributions from land-water, and we rely on a recent expert elicitation assessment for Greenland and Antarctic ice-sheets. We consider two future emissions scenarios and three time horizons that are critical for risk-averse stakeholders (2050, 2100 and 2200). We present our results from global to regional scales and highlight HESs spatial divergence and their departure from global HESs through twelve coastal city and island examples. For HESs-A, the global mean-sea level (GMSL) is projected to reach 1.06(1.91) in the low(high) emission scenario by 2100. For HESs-B, GMSL may be higher than 1.69(3.22) m by 2100. As far as 2050, while in most regions SLR may be of the same order of magnitude as GMSL, at local scale where ice-sheets existed during the Last Glacial Maximum, SLR can be far lower than GMSL, as in the Gulf of Finland. Beyond 2050, as sea-level continue to rise under the HESs, in most regions increasing rates of minimum(maximum) HESs are projected at high(low-to-mid) latitudes, close to (far from) ice-sheets, resulting in regional HESs substantially lower(higher) than GMSL. In regions where HESs may be extremely high, some cities in South East Asia such as Manila are even more immediately affected by coastal subsidence, which causes relative sea-level changes that exceed our HESs by one order of magnitude in some sectors.